Innovative approaches to controlled yogurt fermentation using integrated solar PCM systems - Sharanabasava; Chitranayak; Abhinash P; Syed Mansha Rafiq; Minz Ps; Hima John; Seema Ramniwas; Sami Al Obaid; Mohammad Javed Ansari; Robert Mugabi; Gulzar Ahmad Nayik (CyTA - Journal of Food)
This study aimed to devise a novel fermentation unit for yogurt production utilizing phase change materials (PCM) and primarily powered by solar energy. The unit comprises a solar flat plate collector (FPC), PCM cells, and a fermentation cabinet equipped with trays. High-density polyethylene (HDPE) cylindrical cells were employed to contain paraffin wax for thermal energy storage. The performance of the integrated solar system for the fermentation process was assessed across different air velocities (1.2 to 1.8 m/s), with the most rapid temperature rise observed at 1.8 m/s. The PCM-based thermal storage exhibited an impressive capability of releasing heat autonomously for 6 hours without sunlight, eliminating the need for external energy sources. PCM’s capacity to store and release thermal energy ensures fermentation stability, even without solar radiation. This innovative approach offers a compelling environmentally friendly solution with significant implications for sustainable yogurt production, paving the way for industrial integration.